Participatory Governance Practices in Incubators in Growing and Developing UMKM in Makassar City - Anniza, Nurul; Hasniati, Hasniati; Ahmad, Badu; Syahribulan, Syahribulan (Journal of Management and Administration Provision, 2024)
Participatory governance practices in the Makassar City MSME incubator involve various parties to support the development of micro, small, and medium enterprises (MSMEs). The Makassar City Cooperative and MSME Service maximizes the role of incubators to assist 3,000 MSMEs, including through training and mentoring in financial management, digital marketing, and improving product quality. The purpose of the Inclusive Governance Research on the MSME Incubator program at the Makassar City Cooperative and MSME Service is to describe and analyze participatory governance practices in the Incubators in growing and developing MSMEs in Makassar City. This study uses a descriptive qualitative research method, with data collection techniques through observation, interviews, and documentation. The results of this study are Participatory Governance Practices on Inclusive Governance at the Makassar City Incubator Center show that community participation in the Makassar City incubator center program is not optimal. Although there are many benefits felt by the community in terms of improving business quality, income, consumers and business relations, participation in following all stages of the incubation process is still lacking. Based on data from the Cooperatives and SMEs Service, there are 2,162 MSMEs that entered the pre-incubation stage. However, after the classification curation was carried out, only 510 MSMEs passed the incubation stage, and only 113 reached the acceleration stage.